Influence of Mothers' Dental Anxiety and Perception of Child's OHRQoL Towards Utilization of Dental Services − A Questionnaire Study - Kruthika Murali; Shankar Shanmugam (Wolters Kluwer Medknow Publications, 2017)
Introduction: Dental caries is one of the most common oral health problems in childhood. As a child depends entirely on the parents, its dental visit could be influenced by various psychosocial factors such as parental perceptions of the child's oral health and maternal anxiety. Aim: To assess the influence of children's clinical condition, mothers' dental anxiety and their use of dental services, maternal perception of child's oral health-related quality of life (OHRQoL) on the child's utilization of dental services. Materials and Methods: A cross-sectional survey was conducted among 600 mothers of children between 2 and 5 years of age. The questionnaire included the background characteristics, mothers and child's dental visit, mothers' dental anxiety using Corah's Dental Anxiety Scale and maternal perceptions of the child's OHRQoL using Early Childhood Oral Health Impact Scale. Clinical examination for assessing the dental caries among the children was performed. The data were analyzed using the Statistical Package for the Social Sciences version 17.1 software. Results: Using the final model of Poisson regression analysis with robust variance and forward stepwise procedure, it was found that the age of mother, the age of child, the income of the family, poor OHRQoL, the presence of caries and pain in child significantly influenced the visit of the child to dentist (P ≤ 0.05). No statistically significant association was found between the anxiety of mother and the child's visit. Conclusion: Lack of maternal knowledge, low socio-economic reasons and maternal perception of child's oral health could be the important reasons for a child's less number of dental visits.